Pengaruh Proses Rekrutmen Pegawai PPNPN Badan Narkotika Nasional Provinsi Jawa Barat Terhadap Kinerja Pegawai - Rizki, Aldo Ginanjar; Adji, Widwi Handari (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The purpose of conducting this research is to find out whether the PPNPN recruitment of the national narcotics agency in West Java province has an effect on employee performance . In this study the researchers used a quantitative approach research method with 39 participants with a 95% confidence level and carried out one of the tests, namely the linear regression test simple and using the SPSS V.25 application and the results of this study indicate that the recruitment has a significant effect on employee performance. Keywords: Recruitment; Employee performance